Evaluation of the quality of published SCI clinical practice guidelines using the AGREE II instrument: Results from Can-SCIP expert panel. (30th September 2021) - Patsakos, Eleni M.; Craven, B. Catharine; Kua, Ailene; Cheng, Christiana l.; Eng, Janice; Ho, Chester; Noonan, Vanessa K.; Querée, Matthew; Bayley, Mark T.; ,
Abstract : Introduction: Spinal cord injury (SCI) is a complex condition with substantial adverse personal, social and economic impacts necessitating evidence-based inter-professional care. To date, limited studies have assessed the quality of clinical practice guidelines (CPGs) within SCI. The aim of this study is to evaluate the quality of the development process and methodological rigour of published SCI CPGs across the care continuum from pre-hospital to community-based care. Methods: Electronic health databases and indexes were searched to identify English or French language CPGs within SCI published within the last nine years with specific evidence-based recommendations applicable to the Canadian health care setting. Eligible CPGs were evaluated using the Appraisal of Guidelines for Research and Evaluation II (AGREE II) instrument. Results: A total of forty-one CPGs that met the inclusion criteria were appraised by at least four raters. There was high variability in quality. Twenty-seven CPGs achieved a good rigour of development domain score of >70%. Other standardized mean domain scores were scope and purpose (85.32%), stakeholder involvement (65.03%), clarity of presentation (84.81%), applicability (55.55%) and editorial independence (75.83%). The agreement between appraisers (intraclass correlation coefficient) was high (intraclass correlation coefficient > 0.80). Conclusion: There is a paucity of CPGs that address community-based specialized rehabilitation and community reintegration. Furthermore, many CPGs only focus on a single impairment at one time point in the care continuum. As SCI is a complex condition that results in multimorbidity and requires health monitoring and intervention across the lifespan, a rigorously developed CPG that addresses high-quality, interprofessional comprehensive care is needed.